MODERN APPROACHES TO THE FORMATION OF LESSON’S EDUCATIONAL GOALS IN PRIMARY SCHOOL - Prokop, I.S. (Pedagogy of Higher and Secondary Education, 2010)
In the article actuality of problems of specification and technology of raising of educate aims of lesson is grounded in the conditions of humanism education, personality oriented teaching, traditional and alternative conceptions of educate aims of lesson are analysed at initial school.